The complex role of telocytes in female prostate tumorigenesis in a rodent model - Maldarine, Juliana S. (2022)
The prostate is not an organ exclusive to the male. It is also found in females of several species, including humans, in which part of the Skene gland is homologous to the male prostate. Evidence is accumulating that changes in the stroma are central to tumorigenesis. Equally, telocytes, a recently discovered type of interstitial cell, are essential for the maintenance of stromal organization. However, it is still uncertain whether there are telocytes in the female prostate and if they play a role in tumorigenesis. The present study used ultrastructural and immunofluorescence techniques to investigate the presence of telocytes in the prostate of Mongolian gerbil females, a rodent model that often has a functional prostate in females, as well as to assess the impact of a combination of N-ethyl-N-nitrosourea, testosterone, and estradiol on telocytes. The results point to the presence of telocytes in the female prostate in the perialveolar and interalveolar regions, and reveal that these cells are absent in regions of benign and premalignant lesions in the gland, in which the perialveolar smooth muscle is altered. Additionally, telocytes are also closely associated with infiltrated immune cells in the stroma. Our data suggest that telocytes are important for both the maintenance of smooth muscle and prostatic epithelium integrity, which indicates a protective role against the advancement of tumorigenesis. But telocytes are also associated with immune cells and a proinflammatory/proangiogenic role for these cells cannot be ruled out, implying that telocytes have a complex role in prostatic tumorigenesis in females.